Kajian Teknis Kinerja Alat Transport Rubber Belt Conveyor pada Pengiriman Batu Kapur ke Storage Pabrik di Departemen Tambang PT. Semen Padang - Ilhami Putra; Tamrin Kasim; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2018)
After doing the observation at PT. Semen Padang, the authors obtained data RKAP (Work Plan and Corporate Budget) of 8,064,608 ton/year and limestone production realization of 7,563,049 ton/year with production percentage 93.8% in 2017. Based on the observation data, it can be seen that limestone mining production target is not always achieved. It is necessary to evaluate the causes of non-achievement of production targets. This can be interpreted that there are problems in the unit crushing and conveying. The problem that often happens is the conveyor belt transportation. PT. Semen Padang itself currently has 3 units of Lime Stone Crusher (LSC). From 3 units of LSC (LSC II, LSC IIIA and LSC IIIB), the total belt conveyor operating on the LSC is 23 belt with different belt width. So also with the speed of each belt is different, depending on the ability of the gearbox mounted on each - each conveyor belt motor. From RBC A2J05 calculation has actual productivity value 813,97 tons/hour, RBC A2J06 has actual productivity value 869,56 tons/hour RBC A4J12P has actual productivity value 1,115,72 tons/hour RBC A1J02 has actual productivity value 1,352,98 tons/hour RBC A1J12B has actual productivity value 1,465,45 tons/hour, RBC A4J14 has actual productivity value 1,091,99 tons/hour. After performing RBC A2J05 performance optimizer, RBC A2J06, RBC A4J12P, RBC A1J02, RBC A1J12B and RBC A4J14 according to gearbox's maximum capability, the A4J12P belt productivity, A1J12B belt, A4J14 belt is able to accommodate limestone delivery, while belt A2J05, belt A2J06 and the A1J02 belt is still unable to accommodate limestone delivery production in December 2017Keywords: Crushing, Conveying, Belt conveyor, Limestone, Gearbox